Efektivitas Manajemen Kepala Sekolah dalam Meningkatkan Kinerja Sekolah (Studi di SMP Negeri 4 Kerajaan Kecamatan Kerajaan Kabupaten Pakpak Bharat) - Padang, Sabar Anggiat Sahata; Pratiwi, Sri Nurabdiah; Sulasmi, Emilda (Jurnal Manajemen Pendidikan Dasar, Menengah dan Tinggi [JMP-DMT], 2024)
This research aims to determine the effectiveness of principal management in improving school performance at SMP Negeri 4 Kerajaan, Kerajaan District, Pakpak Bharat Regency. This research uses a qualitative approach. The data collection tools used were observation, interviews and documentation. Data analysis uses data reduction, data presentation, and drawing conclusions. The research subjects were teachers and principals of SMP Negeri 4 Kerajaan. The results of the research and conclusions are that: 1) The effectiveness of principal's planning in improving performance at SMP Negeri 4 Kerajaan, Kerajaan District, Pakpak Bharat Regency is good, where the principal has prepared an organizational structure, Operational Curriculum of Education Unit (KOSP), School Work Plan (RKS) guide which is prepared from the characteristics, conditions and potential region, socio-cultural community, school potential and student needs and contains all the activities that must be carried out by teachers; 2) The effectiveness of principal's organizing in improving performance at SMP Negeri 4 Kerajaan has been carried out well, where the principal arranges the duties and responsibilities of teachers through MGMP’activities, where MGMP is divided according to subjects and controlled through the chairman. The activities carried out at MGMPs activities are also supported by facilities and infrastructure, however the facilities and infrastructure do not yet support it optimally. 3) The effectiveness of principal’s actuating in improving performance at school has been good, where teachers have carried out their responsibilities well, teachers have provided teaching modules, designed media, disciplined attendance, implemented innovative learning models and comply with applicable regulations. 4)The effectiveness of principal’s supervision (controlling) in improving performance at school is carried out regularly, where the principal observes the performance of each teacher and always carries out evaluations through education supervision and also in order to resolve existing problems in the school.